The Impact of Intra-thoracic Anatomical Changes upon the Delivery of Lung Stereotactic Ablative Radiotherapy. Issue 10 (October 2021) - Brown, S.; Beasley, M.; Aznar, M.C.; Belderbos, J.; Chuter, R.; Cobben, D.; Faivre-Finn, C.; Franks, K.; Henry, A.; Murray, L.; Price, G.; van Herk, M.
Abstract: Aims: So far, the impact of intra-thoracic anatomical changes (ITACs) on patients treated with stereotactic ablative radiotherapy (SABR) for early-stage non-small cell lung cancer is unknown. Studying these is important, as ITACs have the potential to impact the workflow and reduce treatment quality. The aim of this study was to assess and categorise ITACs, as detected on cone beam computed tomography scans (CBCT), and their subsequent impact upon treatment in lung cancer patients treated with SABR. Materials and methods: CBCTs from 100 patients treated with SABR for early non-small cell lung cancer were retrospectively reviewed. The presence of the following ITACs was assessed: atelectasis, infiltrative change, pleural effusion, baseline shift and gross tumour volume (GTV) increase and decrease. ITACs were graded using a traffic light protocol. This was adapted from a tool previously developed to assesses potential target undercoverage or organ at risk overdose. The frequency of physics or clinician review was noted. A linear mixed effects model was used to assess the relationship between ITAC grade and set-up time (time from first CBCT to beam delivery). Results: ITACs were observed in 22% of patients. Twenty-one per cent of these were categorised as 'red', implying a risk of underdosage to the GTV. Most were 'yellow' (51%), indicating little impact upon planning target volume coverage of the GTV. Physics or clinician review was required in 10% of all treatment fractions overall. Three patients needed their treatment replanned. The mixed effect model analysis showed that ITACs cause a significant prolongation of set-up time ( Χ 2 (3) = 9.22, P = 0.02). Conclusion: Most ITACs were minor, but associated with unplanned physics or clinician review, representing a potentially significant resource burden. ITACs also had a significant impact upon set-up time, with consequences for the wider workflow and intra-fraction motion. Detailed guidance on the management of ITACs is needed to provide support for therapeutic radiographers delivering lung SABR. Highlights: ITACs occur not infrequently during the delivery of stereotactic ablative radiotherapy for lung cancer. The development of ITACs represents a resource burden due to the unscheduled clinician and physics involvement. Intra-thoracic anatomical changes have the potential to prolong treatment set-up time.